Analisis Teknik Dasar Shooting Atlet SSB Silampari Tugumulyo - Agriansyah Agriansyah; Azizil Fikri; Muhammad Supriyadi (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2022)
This study aims to determine the basic shooting techniques of SSB Silampari Tugumulyo athletes. The research method used in this research is qualitative, where the data is obtained through interviews, observation, and documentation. The population and sample or research subjects used in this study were SSB Silampari Tugumulyo football players, totaling 20 people. Data collection techniques in this study used various methods, namely interviews, observation, and documentation. The data analysis technique used in this research is qualitative analysis: data reduction, data presentation, and conclusion drawing or verification. While the analysis uses interactive analysis of the three main components. This study uses a qualitative descriptive approach with survey methods data obtained through observation and structured interviews. Then triangulation of data collection techniques is carried out using several methods in data collection, including interviews and observations. Based on the data analysis, the results obtained were that almost all players could perform basic shooting techniques well. The conclusion is that the basic shooting technique of SSB Silampari Tugumulyo Athlete, seen from the aspect of motion observation based on the athlete's ability, is that the average basic shooting technique of SSB Silampari Tugumulyo Athlete can be said to be good and appropriate in theoretical studies. Keywords: Analysis, Shooting Basic Techniques.